Bioinspired Technologies to Connect Musculoskeletal Mechanobiology to the Person for Training and Rehabilitation - Pizzolato, Claudio; Lloyd, David G.; Barrett, Rod S.; Cook, Jill L.; Zheng, Ming H.; Besier, Thor F.; Saxby, David J. (Frontiers in Computational Neuroscience, 2017)
Musculoskeletal tissues respond to optimal mechanical signals (e.g., strains) through anabolic adaptations, while mechanical signals above and below optimal levels cause tissue catabolism. If an individual’s physical behaviour could be altered to generate optimal mechanical signalling to musculoskeletal tissues, then targeted strengthening and/or repair would be possible. We propose new bioinspired technologies to provide real-time biofeedback of relevant mechanical signals to guide training and rehabilitation. In this review we provide a description of how wearable devices may be used in conjunction with computational rigid-body and continuum models of musculoskeletal tissues to produce real-time estimates of localised tissue stresses and strains. It is proposed that these bioinspired technologies will facilitate a new approach to physical training that promotes tissue strengthening and/or repair through optimal tissue loading.